Agronomic, Yield, and Yield Potential of Rainfed Lowland Rice Varieties under Masbate Conditions - Dollison, Mohammad; Basulgan, Eddie B.; Dollison, Beverly B. (Biosaintifika: Journal of Biology & Biology Education, 2025)
The increasing demand for rice as a staple food for Filipinos is important to sustain the country's self-sufficiency in rice. Masbate is an agricultural province of the Bicol region, Philippines, where rice is a staple food and a primary crop produced. Adaptability of improved rice varieties to different locations is important to increase productivity. This study evaluated the agronomic, yield, and yield potential of different rainfed rice varieties under Masbate conditions. The study used a Randomized Complete Block Design (RCBD) with four treatments, replicated three times. Data such as plant height at maturity, days to flowering, productive tillers, number of spikelets per panicle, number of filled grains, the weight of hundred grains in grams, and yield per hectare in tons were gathered. Data were analyzed using the ANOVA in RCBD and a post-hoc analysis using Tukey's HSD test for observed significant differences. The result showed a significant difference in plant height in centimeters, number of spikelets, and percentage of filled grains. However, a nonsignificant difference was obtained in the days to flowering, the number of productive tillers, the weight of a hundred grains, and yield per hectare in tons. Regarding yield and yield potential of different rainfed varieties, the NSIC Rc 272 and NSIC Rc 278 obtained the highest yield performance among the four varieties. The study's findings highlight the potential of different rainfed rice varieties as a new option for rice production. Further research is recommended using different rice varieties developed and fertilizer management practices for better yield output.